Kesantunan Berbahasa Mahasiswa Program Pertukaran Mahasiswa pada Mata Kuliah Modul Nusantara di Politeknik Negeri Semarang - Yusuf Hendrawanto; Eri Prihatmini; Toni Hartono; Rangga Permana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to describe the compliance and violation of language politeness principles in student communication to lecturers via WhatsApp. The background of this research highlights the importance of communication ethics in the academic environment, especially amidst Indonesia's cultural diversity and the dynamics of the Merdeka Belajar Kampus Merdeka (MBKM) program. The method used is a qualitative descriptive method with documentation techniques. The research data sources are utterances in WhatsApp messages from students of the Indonesian Language Education Study Program collected from January to June 2019. Data analysis was carried out through the stages of collection, reading, maxim identification, classification, and analysis. The results showed compliance with five of Leech's politeness maxims: tact maxim (11 data), generosity maxim (2 data), approbation maxim (2 data), agreement maxim (11 data), and sympathy maxim (2 data). Compliance is characterized by the use of greetings, apologies, self-introduction, and providing options to the interlocutor. Meanwhile, violations of politeness principles were found in the tact maxim (4 data) and the agreement maxim (1 data). Violations occurred because students gave the impression of dictating, forcing, or not providing freedom of choice to the lecturers. This study concludes that although most students have implemented politeness, a deeper understanding of speech strategies is still needed to maintain a harmonious relationship between students and lecturers.